Innovative Arabic Language Learning: Redefining Language Archetypes Using Artificial Intelligence - Hadid Asfar; Ilya Husna; Yasmadi Yasmadi; Ashabul Khairi; Karmila Suryani; Al Ikhlas; Ade Sri Madona (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Although Arabic language learning based on Artificial Intelligence (AI) has developed rapidly, comprehensive studies on how this technology is transforming the fundamental paradigms of Arabic language education remain scarce. Therefore, this research aims to explore the changing paradigms of Arabic language learning through the use of AI. This study employs a qualitative descriptive approach and is primarily a literature review. Data were collected from various recent sources, including books, journals, articles, websites, and more. The data collection technique used was documentation, and the analysis was conducted using content analysis. The findings of this study encompass AI-based learning of Arabic vocabulary (mufradat), grammar (qowaid), translation (tarjamah), language skills (maharah), communicative learning, and assessment of Arabic learning. The conclusion drawn from this research is that the use of AI can serve as an interactive tool that enhances students' Arabic language learning abilities and opens up opportunities for more flexible, effective, and efficient educational approaches. Future research could focus on the development of AI tools tailored specifically for different dialects of Arabic and investigate the long-term impact of AI on Arabic language proficiency across diverse learner demographics.